ANALYSIS OF THE XPOSE UNCENSORED PROGRAM IN SHAPING PARENTS’ PERCEPTIONS OF CHILDCARE SECURITY PATTERNS IN ISLAMIC BOARDING SCHOOLS - Zein, Silvia Anggraini; Effendi, Erwan (International Journal of Cultural and Social Science, 2026)
This study examines the influence of television investigative journalism on shifts in the security paradigm within religious education settings. The primary focus of this study is to analyze how the program “Xpose Uncensored” on Trans7 constructs a social reality that shapes public trust. This study employs a qualitative approach using a case study method to explore the psychological dynamics and shifts in the perceptions of boarding school guardians following exposure to dramatic investigative content. Data collection was conducted through in-depth interviews, content observation, and documentation of emerging phenomena during the 2025–2026 period. The results of this study indicate that the program systematically deconstructs traditional pesantren values through three main strategies: the deconstruction of adab values into physical marginalization, economic stigmatization through transactional framing, and the delegitimization of santri service (roan) as labor exploitation. The research findings reveal a significant cultivation effect, in which parents of students experience distorted perceptions on the cognitive, affective, and conative dimensions. The media successfully homogenized the parents’ perspectives into a collective fear (mainstreaming) that transformed the image of the pesantren from a “sacred space” into a “risky feudal institution. As a result, a crisis of public trust has emerged, prompting parents to shift from a trust-based, delegative parenting style to a suspicious, investigative one, and even leading them to consider transferring their children to public schools to ensure their physical and mental safety